An early Pleistocene Mg/Ca‐δ18O record from the Gulf of Mexico: Evaluating ice sheet size and pacing in the 41‐kyr world. (25th July 2016) - Shakun, Jeremy D.; Raymo, Maureen E.; Lea, David W.
Abstract: Early Pleistocene glacial cycles in marine δ 18 O exhibit strong obliquity pacing, but there is a perplexing lack of precession variability despite its important influence on summer insolation intensity – the presumed forcing of ice sheet growth and decay according to the Milankovitch hypothesis. This puzzle has been explained in two ways: Northern Hemisphere ice sheets instead respond to insolation integrated over the summer, which is mostly controlled by obliquity, or anti‐phased precession‐driven variability in ice volume between the hemispheres cancels out in global δ 18 O, leaving the in‐phase obliquity signal to dominate. We evaluated these ideas by reconstructing Laurentide Ice Sheet (LIS) meltwater discharge to the Gulf of Mexico from 2.55‐1.70 Ma using foraminiferal Mg/Ca and δ 18 O. Our δ 18 Osw record displays six prominent anomalies, which likely reflect meltwater pulses, and they have several remarkable characteristics: (1) their presence suggests that the LIS expanded into the mid‐latitudes numerous times; (2) they tend to occur or extend into interglacials in benthic δ 18 O; (3) they generally correlate with summer insolation intensity better than integrated insolation forcing; and (4) they are perhaps smaller in amplitude but longer in duration than their late Pleistocene counterparts, suggesting comparable total meltwater fluxes. Overall, these observations suggest that the LIS was large, sensitive to precession, and decoupled from marine δ 18 O numerous times during the early Pleistocene – observations difficult to reconcile with a straightforward interpretation of the early Pleistocene marine δ 18 O record as a proxy for Northern Hemisphere ice sheet size driven by obliquity forcing at high latitudes. Key Points: Six ice sheet meltwater events identified in Gulf of Mexico seawater δ 18 O record from 2.55‐1.70 Ma Events are typically long, occur late in benthic δ 18 O deglaciations, and line up with summer insolation This challenges view of early Pleistocene marine δ 18 O as simply recording obliquity‐driven Northern Hemisphere ice volume